The Influence of Pancasila and Civic Education Teachers in Shaping the Character of Students as a Response and Challenge of the 21st Century - Rd Sugara Mochamnad Haddad; Ujang Suprihat (CV. Rayyan Dwi Bharata, 2023)
This research was motivated by the discovery of problems such as lack of responsibility, discipline, communication between students, and individualist tendencies. The purpose of this study is to determine and analyze the influence of Pancasaila and Civic Education teachers in shaping the character of students as a response and challenge of the 21st century. Survey research method with quantitative approach. Data collection techniques include questionnaires and documentation. Respondents consisted of 52 students. The results of the study based on calculations using SPSS software version 25 obtained results 1) of 5.8%, this shows that the influence of the contribution of PPKn teachers is low in shaping the character of students at SMA Negeri 1 Subang. 2) by 20.8%, this shows that the influence of PPKn teachers is the level of influence is in shaping the character of students in the 21st century. 3) an influence of 8%, this shows that the influence of PPKn teachers in shaping the character of students is very low before researchers conducted research in grade X of SMA Negeri 1 Subang. 4) by 25.6%. This shows that the influence of PPKn teachers in shaping the character of students has changed the level of change, which is in shaping the character of students as a response and challenge of the 21st century. From these data, it shows that teachers of Pancasila and Civic Education have an influence in shaping the character of students as a response to the challenges of the 21st century. By being influenced by factors such as planning, implementing learning, student conditions, student character, teacher guidance and motivation, teacher social attitudes, and the use of learning facilities.